Adverse events and tolerability of combined durvalumab and tremelimumab versus durvalumab alone in solid cancers: a systematic review and meta-analysis - Fahmy, Omar; Ahmed, Osama A. A.; Khairul-Asri, Mohd Ghani; Alhakamy, Nabil A.; Alharbi, Waleed S.; Fahmy, Usama A.; El-Moselhy, Mohamed A.; Fresta, Claudia G.; Caruso, Giuseppe; Caraci, Filippo (Multidisciplinary Digital Publishing Institute, 2022)
Background: Recently, the combination of durvalumab and tremelimumab, two immune checkpoint inhibitors, for the treatment of different types of cancers has been considered; however, its overall effects, including its safety, are still unclear and need to be further investigated. Objectives: The aim of the present systematic review and meta-analysis was to investigate the safety and tolerability of this combination of drugs. Methods: A systematic review of the literature, based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement, was conducted by employing online electronic databases and the American Society of Clinical Oncology (ASCO) Meeting Library. The selection of eligible publications was made following a staged screening and selection process. The software RevMan 5.4 was used to run the quantitative analysis and forest plots, while the Cochrane tool was employed for risk of bias assessment. Results: From the retrieved 157 results, 9 randomized controlled trials involving 3060 patients were included. By comparing the combination of durvalumab and tremelimumab vs. durvalumab monotherapy, it was observed that: adverse events (AEs) ≥ Grade 3 incidence was 32.6% (536/1646) vs. 23.8% (336/1414) (Z = 2.80; p = 0.005; risk ratio (RR) = 1.44), reduced appetite incidence was 10.8% (154/1427) vs. 8.3% (108/1305) (Z = 2.26; p = 0.02; RR = 1.31), diarrhea was reported in 15.6% (229/1473) vs. 8.1% (110/1352) (Z = 5.90; p < 0.00001; RR = 1.91), rash incidence was equal to 11.1% (160/1441) vs. 6.5% (86/1320) (Z = 4.35; p <0.0001; RR = 1.75), pruritis was 13.6% (201/1473) vs. 7.7% (104/1352) (Z = 5.35; p < 0.00001; RR = 1.83), fever was 10.5% (42/399) vs. 6.6% (22/330) (Z = 2.27; p = 0.02; RR = 1.77), discontinuation rate was 18% (91/504) vs. 3% (36/434) (Z = 4.78; p < 0.00001; RR = 2.41), and death rate was 2.6% (13/504) vs. 0.7% (3/434) (Z = 1.90; p = 0.06; RR = 2.77). Conclusions: It was observed that the combined (durvalumab and tremelimumab) vs. monotherapy (durvalumab) is associated with a higher risk of treatment discontinuation, mortality, fever, diarrhea, rash, pruritis, and reduced appetite. This information is relevant and should be disclosed, especially to patients that are currently enrolled in clinical trials considering this combined therapy.